Cooperating with your romantic partner: Associations with interpersonal emotion coordination. (December 2013) - Randall, Ashley K.; Post, Jesi H.; Reed, Rebecca G.; Butler, Emily A.
Romantic partners' emotions become coordinated in various ways and this may have implications for well-being (Butler (2011) Temporal interpersonal emotion systems: The "TIES" that form relationships. Personality and Social Psychology Review, 15, 367–393.). The present study uses a community sample of 44 committed heterosexual couples to examine whether cooperation, a generally beneficial relational process, is associated with emotional coordination and whether the pattern differs when men's emotions are coordinated with their female partners' prior emotions or vice versa. Using behavioral observations of cooperation and second-to-second measures of emotional experience during a face-to-face conversation, men showed the most positive emotional experience at high levels of mutual cooperation. As predicted, cooperation was associated with different coordination patterns for men and women, with high mutual cooperation predicting an inphase pattern for men (emotions changing in unison with their partners) and an antiphase pattern for women (emotions changing in opposite directions from their partners). Our results suggest that men and women may experience cooperation differently, despite engaging in similar behaviors.